Increasing Entrepreneurial Interest through Entrepreneurship Education: The Important Role of Self-Efficacy - Hengky Widhiandono; Diastuti Yuliawati (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2024)
This research aims to add evidence to previous studies on the effect of entrepreneurial education and self-efficacy on entrepreneurial interest, as well as the moderating effect of the influence between entrepreneurial education and entrepreneurial interest. The population of this study consists of 398 students from the Faculty of Economics and Business at Universitas Muhammadiyah Purwokerto, who have completed six semesters of entrepreneurial education. The sampling technique used is cluster sampling, with a sample size of 200 students. Data collection was conducted using a questionnaire. Data analysis was performed using Smartpls software for validity, reliability, model fit, and t-test analysis. The study results conclude that entrepreneurial education positively and significantly increases students' entrepreneurial interests. Additionally, self-efficacy has a positive significant effect on students' entrepreneurial interests. However, self-efficacy needs to moderate the influence between entrepreneurial education and students' entrepreneurial interests.